Management and Malignancy Rate of Thyroid Nodules with a Cytologic Diagnosis of Atypia or Follicular Lesion of Undetermined Significance - Carlos, Armi Dianne; Mirasol, Roberto; Thomas Aquino, Eduardo; Lourdes Goco, Maria; Rizelle Toledo, Pauline; Carl Santos, Kevin (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Objective. This study describes the clinical data of adult patients who underwent Fine Needle Aspiration Biopsy (FNAB) of thyroid nodule(s) with a cytologic diagnosis of Atypia or Follicular Lesion of Undetermined Significance (AUS or FLUS) at St. Luke’s Medical Center from January 2012 to October 2013. Methodology. Adult patients who underwent FNAB of the thyroid nodule with a cytologic diagnosis of AUS or FLUS were studied retrospectively using the ultrasound result, initial consultation form and operative techniques of these patients. The cytologic and histopathologic diagnoses were retrieved through the electronic Healthcare-Results Management System. Results and Conclusion. A third (34%) of the patients with a cytologic diagnosis of AUS or FLUS (8.9%) underwent surgery. Of the 68 patients who underwent surgery, 44 were benign and 24 were malignant with a malignancy rate of 35.3%. Preoperatively, there were no ultrasound characteristics or microscopic descriptions significantly associated with malignancy. The recommendation of the Bethesda System to do a repeat FNAB in these thyroid nodules should, therefore, be reconsidered.